Self-propulsion of bent bimetallic Janus rods. (26th October 2018) - Venkateshwar Rao, Dugyala; Reddy, Naveen; Fransaer, Jan; Clasen, Christian
Abstract: In this paper, the sideways self-propulsion behaviour of straight and bent Janus micro-rods is presented. Janus micro-rods are prepared by consecutively sputter-coating platinum and gold on different sides of aligned polystyrene micro-fibers produced via electrospinning. Self-propulsion is induced via the reaction of hydrogen peroxide at the Janus particle interface, and the effect of the particles shape on their self-propulsion trajectories is studied. We show that the self-propulsion trajectories change from straight to circular when the particle shape is changed from a straight to an 'L' shaped rod. In order to understand and quantitatively describe the particle shape effects, we adopted a mathematical model developed by Hagen et al (2011 J. Phys.: Condens. Matter .23 194119) to predict their trajectories. We show that the trajectory of irregularly shaped micro-rods depends only on the particle shape. The predicted trajectories for various particle shapes are in good agreement with the experimental observations.